Together We Rise: How Social Movements Succeed - Nardini, Gia; Rank‐Christman, Tracy; Bublitz, Melissa G.; Cross, Samantha N. N.; Peracchio, Laura A. (Journal of Consumer Psychology, 2021)
Social movements, such as Black Lives Matter, surge when support grows for their social justice goals. At their core, social movements advance when people act collectively by rising in solidarity with a shared purpose to address injustice and inequality. Drawing on insights from consumer psychology, this review investigates how social movements succeed in creating social change. We build on an established 21st‐century framework for how social movements succeed to outline the promising practices of successful social movements. For each of these practices, we identify the consumer psychology mechanisms that motivate collective action and encourage people to transform from bystanders to upstanders, those who provide the grassroots momentum for successful social movements. We illustrate this framework with examples from the growth of the Black Lives Matter movement. Finally, we highlight insights from consumer psychology that promote an understanding of social movements, and we raise research questions to encourage more consumer psychologists to investigate how social movements succeed.